Cross-Talk Between TGF-β and NADPH Oxidases During Liver Fibrosis and Hepatocarcinogenesis - Crosas-Molist, Eva; Bertran, Esther; Fabregat, Isabel (Current Pharmaceutical Design, 2015)
Liver fibrosis is a pathological consequence of chronic liver diseases and results from the progressive accumulation of altered extracellular matrix, highly enriched in type I and III fibrillar collagens. In advanced stages, fibrosis leads to cirrhosis, defined by abnormal liver architecture and altered vascularization. Clinical consequences of cirrhosis are failure in the synthetic function of the liver, portal hypertension, high susceptibility to infection and high risk to develop hepatocellular carcinoma (HCC). The TGF-β family of cytokines plays essential roles in many cellular processes, including growth inhibition, cell migration and invasion, extracellular matrix remodelling and immune suppression, being involved in the maintenance of tissue homeostasis. However, TGF-βs are often continuously overexpressed in disease states, such as fibrosis, inflammation and cancer, and they play pivotal roles in the sequence of events leading to end-stage of chronic liver diseases. Reactive oxygen species (ROS) are critical intermediates in liver physiology and pathology. When the equilibrium between ROS generation and the antioxidant defence of the cell is disrupted, it results in an oxidative stress process. The NADPH oxidase (NOX) family has emerged in the last years as important source of ROS in liver pathologies. Interestingly, NOXes mediate TGF-β actions in liver cells, such as regulation of hepatocyte growth and death, as well as activation of hepatic stellate cells to myofibroblasts, key executers of the fibrotic process. In this review we will update the relevant and differential roles of NOX isoforms during liver fibrosis and hepatocarcinogenesis, their cross-talk with the TGF-β pathway and their potential as therapeutic targets for these diseases.
Keywords: liver cancer